Marking documents with executable text for processing by computing systems (2015)
Techniques for processing documents with executable text are disclosed. The techniques, among other things, can effectively address XSS attacks to Internet users when browsing web sites. Content deemed not to be trusted or fully trusted ("untrusted") can be marked in a document that can include executable text. Remedial action, including not allowing execution of executable text marked as "untrusted" can be taken. In addition, when the document is processed, content deemed not to be trusted or fully trusted ("untrusted") can be effectively monitored in order to identify executable text that may have been effectively produced by "untrusted" content and/or somehow may have been affected by "untrusted" content.